2011
DOI: 10.1093/eurpub/ckr036
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of blood pressure distribution in school children

Abstract: It is therefore recommended that the children must be screened regularly for blood pressure to detect the prevalence so that remedial measure may be initiated as early as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…[61011172526] In the current study, both SBP and DBP were found to be significantly correlated with BMI. Present study results, obtained after multivariate analysis, strengthen the independent association of BMI with BP.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…[61011172526] In the current study, both SBP and DBP were found to be significantly correlated with BMI. Present study results, obtained after multivariate analysis, strengthen the independent association of BMI with BP.…”
Section: Discussionmentioning
confidence: 59%
“…[89] Further, a number of environmental factors have been found to be associated with hypertension in children and adolescents. [10] Thus, early detection of hypertension and its aggravating factors becomes imperative. The data on blood pressure (BP) profile of school adolescents is scanty in India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] A number of environmental and genetic factors are associated with hypertension such as age, sex, body size, obesity, change in dietary habits and family history of hypertension, physical activity, and increased stress. [4] Hypertension is emerging as a major health problem. The prevalence of hypertension has increased in urban communities as well as in rural people.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de realizados em adolescentes, estudos tem evidenciado correlação importante entre a PAS e PAD e a idade 59,136 , o que corrobora as alterações da PA em função da idade aqui encontradas.. Figura 12 -Relação da Pressão arterial sistólica (PAS) dos escolares com escore z de estatura (HAZ). .…”
Section: Pressão Arterial E Idadeunclassified